2016
DOI: 10.1038/srep27812
|View full text |Cite
|
Sign up to set email alerts
|

Preserved neurogenesis in non-demented individuals with AD neuropathology

Abstract: Rare individuals remain cognitively intact despite the presence of neuropathology usually associated with fully symptomatic Alzheimer’s disease (AD), which we refer to as Non-Demented with Alzheimer’s disease Neuropathology (NDAN). Understanding the involved mechanism(s) of their cognitive resistance may reveal novel strategies to treat AD-related dementia. In the pursuit of this goal, we determined the number of hippocampal neural stem cells (NSCs) and investigated the expression of several miRNAs in NDAN and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 33 publications
6
65
0
Order By: Relevance
“…Interestingly, eleven proteins from our dataset cluster into the nervous system development and function pathway. This is consistent with our previous findings showing that when compared to AD and MCI, NDAN individuals have higher rate of neurogenesis in the dentate gyrus, which is positively correlated to their ability to escape (or significantly delay) dementia [51]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, eleven proteins from our dataset cluster into the nervous system development and function pathway. This is consistent with our previous findings showing that when compared to AD and MCI, NDAN individuals have higher rate of neurogenesis in the dentate gyrus, which is positively correlated to their ability to escape (or significantly delay) dementia [51]. …”
Section: Resultssupporting
confidence: 93%
“…UCHL1 is expressed mostly by neurons and neuroendocrine cells, and it was found in Lewy bodies [122] and NFTs [123]. Interestingly, Lombardino et al showed that replaceable neurons have lower levels of UCHL1 when compared to non-replaceable neurons [124], which can be in concordance with the increased neurogenesis in NDAN [51] one of the hypothesis behind NDAN preserved cognitive function.…”
Section: Discussionmentioning
confidence: 95%
“…In particular, older adults with high levels of exposure to particulate air pollution show poorer cognitive outcomes than non-exposed individuals (Ailshire and Clarke 2015). Aberrant neurogenesis is associated with poor cognitive functioning, and even individuals having characteristic AD neuropathology show no impairment of cognitive functions when neurogenesis is conserved (Briley et al 2016). These considerations should, however, be tempered by the fact that in the present study, the persistence over time of the effect of DE on neurogenesis was not assessed and that an assessment of cognitive behavior was not carried out.…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the postsynaptic proteome of such NDAN individuals provides some veracity to this hypothesis identifying a unique proteomic signature for the NDAN postsynaptic densities (Zolochevska, Bjorklund, Woltjer, Wiktorowicz, & Taglialatela, ). Enhanced neurogenesis may also play a part, and these dementia‐resistant subjects also show an increased number of neural stem cells and new neurons in the hippocampal dentate gyrus as well as a unique expression of neurogenesis‐regulating miRNAs (Briley et al, ). These observations in themselves may provide new neuroprotective strategies and therapeutic targets in the search for novel treatments for AD.…”
Section: Pathways To Amyloid Its Clearance and Neuronal Toxicitymentioning
confidence: 99%